2009
DOI: 10.1509/jmkr.46.6.739
|View full text |Cite
|
Sign up to set email alerts
|

Supersize in One Dimension, Downsize in Three Dimensions: Effects of Spatial Dimensionality on Size Perceptions and Preferences

Abstract: for their help with the data collection. Dominique Hanssens served as associate editor for this article. PIERRE CHANDON and NAILYA ORDABAYEVA* Understanding consumer response to product supersizing and downsizing is important for policy makers, consumer researchers, and marketers. In three laboratory experiments and two field studies, the authors find that changes in size appear smaller when packages and portions change in all three spatial dimensions-height, width, and length-than when they change in only one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(95 citation statements)
references
References 32 publications
4
86
0
1
Order By: Relevance
“…Our results show that there is little distinction between manipulating a plate in two dimensions (area) or three dimensions (volume as in a bowl). Moreover, if there were to be a difference, we would expect twodimensional changes to have a greater effect than threedimensional changes in view of the compelling evidence that the perceived size and perceived change in size in containers is quite distinct from the actual change (Chandon and Ordabayeva 2009;Ordabayeva and Chandon 2013). Changes in one dimension are generally perceived as bigger than an equivalent change in three dimensions (Raghubir and Krishna 1999;Chandon and Ordabayeva 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that there is little distinction between manipulating a plate in two dimensions (area) or three dimensions (volume as in a bowl). Moreover, if there were to be a difference, we would expect twodimensional changes to have a greater effect than threedimensional changes in view of the compelling evidence that the perceived size and perceived change in size in containers is quite distinct from the actual change (Chandon and Ordabayeva 2009;Ordabayeva and Chandon 2013). Changes in one dimension are generally perceived as bigger than an equivalent change in three dimensions (Raghubir and Krishna 1999;Chandon and Ordabayeva 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Given this difficulty in interpreting percentages, consumers may be more susceptible to influences of a coloured area on pack. In another stream of research, consumer perceptions have been shown to depend on the spatial dimensionality of product packages (Chandon and Ordabayeva 2009;Wansink and van Ittersum 2003). That is, consumers perceive tall and narrow containers differently from short and wide containers, even when objectively their volume is the same.…”
Section: The Anchoring Effect In the Mars Casementioning
confidence: 99%
“…According to Wansink and Sobal (2007), adults typically make more than 200 food-related decisions per day, but they are consciously aware of only 14.4 of these choices. Many cues (e.g., odours, images, messages) are present in the daily environment (Chandon & Ordabayeva, 2009;Coelho, Polivy, Herman, & Pliner, 2009;Fedoroff, Polivy, & Herman, 2003;Ferriday & Brunstrom, 2008;Harris, Bargh, & Brownell, 2009) and may affect eating behaviour and, more precisely, food choice behaviour, but people are not necessarily conscious of the impact of these cues (see Wansink, 2004 for a review). Understanding the impact of non-attentively perceived cues involved in eating behaviour requires the contribution of psychology and cognitive sciences, domains in which several paradigms have been developed to explore non-conscious influences.…”
Section: Introductionmentioning
confidence: 99%